ANALISIS VARIABEL-VARIABEL YANG MEMPENGARUHI SISTEM FISKAL MIGAS (STUDI DI PT. CHEVRON PACIFIC INDONESIA) Variables Affecting Oil and Gas Fiscal System (A Case Study at PT. Chevron Pacific Indonesia - Manungkalit, Rosetti Fabiola (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Exploration and development activity has been negatively impacted by regulatory and fiscal uncertainty, with the 2012 dissolution of BPMIGAS. The lack of clear regulation creates legal uncertainty for the industry. The design should guarantee openness and transparency in the petroleum fiscal systems. Transparency and accountability play crucial roles in ensuring successful of oil and gas fiscal system for the benefit of the people. The governments need to review fiscal terms to maintain attractiveness and investment in oil and gas industry. The purpose of this research is to discover the variables that affect oil and gas fiscal system. The appropriate method for this research is the Partial Least Square (PLS) which can be used mainly as a causal model testing. Analysis results showed that the liberalization of oil and gas, management of upstream oil and gas, and government take influence significant effect to oil and gas fiscal systems. Oil and gas tax system and oil and gas insignificantly influence oil and gas fiscal systems.Keywords: oil and gas fiscal systems, liberalization of oil and gas, management of upstream oil and gas, government take, oil and gas tax system, oil and gas contract framework, Partial Least Square (PLS).